Trachoma elimination in Latin America: prioritization of municipalities for surveillance activities - Martha Idalí Saboyá-Díaz; Angel F. Betanzos-Reyes; Sheila K. West; Beatriz Muñoz; Luis Gerardo Castellanos; Marcos Espinal (Pan American Health Organization, 2019)
Objective. To identify and prioritize municipalities in 22 countries of Latin America for trachoma surveillance activities, to measure the absence or prevalence of trachoma, and to support validation and trachoma elimination efforts in the Region of the Americas. Methods. A prioritization scale was developed in 2017 to rank each municipality by considering a combination of three characteristics: (a) its trachoma vulnerability index, derived from three socioeconomic factors known to be risks for trachoma-lack of access to improved sanitation, to clean drinking water, and to adequate education, according to housing census data from early 2017; (b) its history of trachoma in countries where the disease was not a known public health problem in 2016; and (c) whether or not it shares a border with a municipality where trachoma was a known public health problem in 2016. Municipalities in 22 countries were classified as either very high, high, medium, or low priority for trachoma surveillance. From the Caribbean, only Trinidad and Tobago met inclusion criteria. Results. The prioritization scale identified 1 053 municipalities in Brazil, Colombia, and Guatemala as very high priority for trachoma surveillance. In Ecuador, El Salvador, Guyana, Paraguay, Peru, Suriname, and Venezuela, 183 municipalities were ranked as high priority, and in Argentina, Belize, Bolivia, Chile, Dominican Republic, Honduras, Nicaragua, Panama, and Uruguay, 677 municipalities were designated a medium priority for trachoma surveillance. Conclusions. This prioritization scale will be useful to countries in Latin America that still need to ascertain their current trachoma situation. The absence or prevalence of trachoma in countries designated as very high and high priority for trachoma surveillance activities must be studied to determine the extent of the disease in Latin America.